A survey-based cross-sectional study of doctors' expectations and experiences of non-technical skills for Out of Hours work. Issue 2 (16th February 2015) - Brown, Michael; Shaw, Dominick; Sharples, Sarah; Jeune, Ivan Le; Blakey, John
Abstract : Objectives: The skill set required for junior doctors to work efficiently and safely Out of Hours (OoH) in hospitals has not been established. This is despite the OoH period representing 75% of the year and it being the time of highest mortality. We set out to explore the expectations of medical students and experiences of junior doctors of the non-technical skills needed to work OoH. Design: Survey-based cross-sectional study informed by focus groups. Setting: Online survey with participants from five large teaching hospitals across the UK. Participants: 300 Medical Students and Doctors Outcome measure: Participants ranked the importance of non-technical skills, as identified by literature review and focus groups, needed for OoH care. Results: The focus groups revealed a total of eight non-technical skills deemed to be important. In the survey 'Task Prioritisation' (mean rank 1.617) was consistently identified as the most important non-technical skill. Stage of training affected the ranking of skills, with significant differences for 'Communication with Senior Doctors', 'Dealing with Clinical Isolation', 'Task Prioritisation' and 'Communication with Patients'. Importantly, there was a significant discrepancy between the medical student expectations and experiences of doctors undertaking work. Conclusions: Our findings suggest that medical staff particularly value task prioritisation skills; however, these are not routinely taught in medical schools. The discrepancy between expectations of students and experience of doctors reinforces the idea that there is a gap in training. Doctors of different grades place different importance on specific non-technical skills with implications for postgraduate training. There is a pressing need for medical schools and deaneries to review non-technical training to include more than communication skills.